Psychological correlates of COVID-19 conspiracy beliefs and preventive measures: Evidence from Turkey - Alper, Sinan; Bayrak, Fatih; Yilmaz, Onurcan (Current psychology (New Brunswick, N.J.), 2021)
COVID-19 pandemic has led to popular conspiracy theories regarding its origins and widespread concern over the level of compliance with preventive measures. In the current preregistered research, we recruited 1088 Turkish participants and investigated (a) individual differences associated with COVID-19 conspiracy beliefs; (b) whether such conspiracy beliefs are related to the level of preventive measures; and (c) other individual differences that might be related to the preventive measures. Higher faith in intuition, uncertainty avoidance, impulsivity, generic conspiracy beliefs, religiosity, and right-wing ideology, and a lower level of cognitive reflection were associated with a higher level of belief in COVID-19 conspiracy theories. There was no association between COVID-19 conspiracy beliefs and preventive measures while perceived risk was positively and impulsivity negatively correlated with preventive measures. We discuss the implications and directions for future research.